2004
DOI: 10.1124/jpet.104.074195
|View full text |Cite|
|
Sign up to set email alerts
|

RETRACTION: 5-aza-Cytidine Is a Potent Inhibitor of DNA Methyltransferase 3a and Induces Apoptosis in HCT-116 Colon Cancer Cells via Gadd45- and p53-Dependent Mechanisms

Abstract: Methyltransferase inhibitors commonly used in clinical trials promote tumor cell death, but their detailed cytotoxic action is not yet fully understood. A deeper knowledge about their apotosis-inducing mechanisms and their interaction with DNA methyltransferases (DNMTs) DNMT1, DNMT3a, and DNMT3b might allow the design of more effective drugs with lower cytotoxicity. 5-aza-cytidine (5-aza-CR), a potent inhibitor of DNMT1, is known to induce demethylation and reactivation of silenced genes. In this study, we inv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
89
1
2

Year Published

2005
2005
2019
2019

Publication Types

Select...
8
2

Relationship

1
9

Authors

Journals

citations
Cited by 109 publications
(100 citation statements)
references
References 30 publications
8
89
1
2
Order By: Relevance
“…Given that the HIF-1α SNP C1772T (9), the DNA repair gene XRCC3 (10) SNP and the E-cadherin gene SNP -347 G→GA (11) and -160 C→A (12) are associated with the genetic susceptibility to CRC, DNMT3A is responsible for DNA methylation as a de novo methyltransferase in the tumorigenesis of numerous types of cancer, including CRC. Previous studies have suggested that ectopic DNMT3A expression plays a significant role in CRC progression (13,14). The restriction of Dnmt3a overexpression showed hypermethylation-mediated transcriptional silencing of the Wnt antagonist Sfrp5, and to a lesser extent, Sfrp1 (4).…”
Section: Discussionmentioning
confidence: 98%
“…Given that the HIF-1α SNP C1772T (9), the DNA repair gene XRCC3 (10) SNP and the E-cadherin gene SNP -347 G→GA (11) and -160 C→A (12) are associated with the genetic susceptibility to CRC, DNMT3A is responsible for DNA methylation as a de novo methyltransferase in the tumorigenesis of numerous types of cancer, including CRC. Previous studies have suggested that ectopic DNMT3A expression plays a significant role in CRC progression (13,14). The restriction of Dnmt3a overexpression showed hypermethylation-mediated transcriptional silencing of the Wnt antagonist Sfrp5, and to a lesser extent, Sfrp1 (4).…”
Section: Discussionmentioning
confidence: 98%
“…In addition, 5-azadC was also demonstrated to be a potent inhibitor of DNMT1 and DNMT3a, but not of DNMT3b, expression in HCT116. 58 It remains thus possible that the de novo methyltransferases of DNMT3 family proteins function redundantly to maintain the methylation state.…”
Section: Methodsmentioning
confidence: 99%
“…Yet, although it is possible that the specific cell system (and associated variations in integrity of p53-dependent apoptosis; refs. [29][30][31] contribute to the confusion in the literature, our findings raise alternative hypotheses relevant to more rational future use of hypomethylating agents.…”
Section: Discussionmentioning
confidence: 77%